Aetiological doctrines and prevalence of pellagra: 18th century to middle 20th century - Margaretha Viljoen; Priyesh Bipath; Johannes L. Roos (South African Journal of Science, 2018)
Pellagra is characterised by dermatological, gastrointestinal and neuropsychiatric manifestations. Millions contracted the disease and hundreds of thousands died between the time it was first recorded until pellagra was finally recognised as a niacin-deficiency disease. Pellagra became epidemic when maize, with its limited bio-availability of nutrients such as niacin and tryptophan, became the staple food in the near-monophagic diets of the impoverished and institutionalised. By the mid-20th century, pellagra was all but eradicated in large parts. The decline in prevalence can largely be ascribed to a better understanding of the link between nutrition and disease, improvements in socio-economic conditions of workers and food enrichment. We briefly review aetiological doctrines on pellagra and the global spread of the disease from the early 18th century until the middle of the 20th century. In the final analysis, we examine the reasons for, and the legitimacy of, the persistent association between pellagra and the consumption of maize.